Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1017/s2045796018000148
|View full text |Cite
|
Sign up to set email alerts
|

Children of parents who have been hospitalised with psychiatric disorders are at risk of poor school readiness

Abstract: Children of parents who have been hospitalised with psychiatric disorders are at risk for poor school readiness. These findings add support to recommendations that mental health professionals consider dependent children in discharge and treatment planning for adult psychiatric inpatients. It is also important to ensure that the impact of psychiatric illness in fathers is not overlooked in assessment and intervention. Family-based approaches to adult psychiatric care could meet the dual needs of intervention fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 74 publications
2
20
0
2
Order By: Relevance
“…Our results also support previous evidence showing that having a history of admissions for mental health or behavioural conditions or adversity is an important potential risk indicator for poor infant outcomes that should be considered when supporting individual women in clinical practice. 18 A UK study using primary care records showed that a majority of mothers registered with a general practice had received mental health treatment or diagnosis between the birth of their child and the child's 16th birthday. 37 Parental mental health is strongly linked to child and adolescent mental health and mortality in early adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also support previous evidence showing that having a history of admissions for mental health or behavioural conditions or adversity is an important potential risk indicator for poor infant outcomes that should be considered when supporting individual women in clinical practice. 18 A UK study using primary care records showed that a majority of mothers registered with a general practice had received mental health treatment or diagnosis between the birth of their child and the child's 16th birthday. 37 Parental mental health is strongly linked to child and adolescent mental health and mortality in early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 10 , 11 , 12 , 13 , 14 , 15 , 16 Routine hospital records can be used to identify psychosocial risk factors and their influence on child outcomes. 11 , 17 , 18 , 19 However, most previous studies focused on single risk factors, and there is a gap in the evidence on which of these risk factors—when considered together—are associated with the highest risk. There is an absence of studies using routine records to explore multiple psychosocial risk factors across maternal age groups, before and during early pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other children, those growing up with a parent with a mental illness are at risk of a range of adverse behavioural, developmental and emotional outcomes (13). Bell et al (4) found that children of parents who had been hospitalized for a mental illness were much less likely to be school ready. Difficulties with schooling have also been shown in Sweden where Hjern et al highlighted that twice as many children whose parents had been hospitalised for a mental illness had lower school results and were not able to start secondary education, compared to children without parental mental illness (5).…”
Section: Introductionmentioning
confidence: 99%
“…This included scholastic/language and particularly school attendance. Other research supports this finding with Bell et al (2018) recently highlighting the poor school readiness of children starting primary school when their parents had been hospitalized for a psychiatric condition, compared to their age-typical peers. A Swedish study by Hjern et al (2017) revealed that double the number of children whose parents had been hospitalized for a mental illness showed lower results at school and were unable to commence secondary education, compared to children without parental mental illness.…”
Section: Discussionmentioning
confidence: 61%